A support framework to facilitate social learning and integration skills of first-year undergraduate medical students - Tlalajoe-Mokhatla, N.; van der Merwe, L. J.; Jama, M. P. (South African Medical Association, 2024)
𝗕𝗮𝗰𝗸𝗴𝗿𝗼𝘂𝗻𝗱. Limited research exists on medical students’ coping and adjustment skills, especially in the South African context. Stakeholders planning medical curricula need to be aware of emotional and communication skills that allow students to cope and adjust to stress associated with transitioning to medical studies. 𝗢𝗯𝗷𝗲𝗰𝘁𝗶𝘃𝗲. To design a support framework to facilitate first-year undergraduate medical students’ social learning and integration skills. 𝗠𝗲𝘁𝗵𝗼𝗱𝘀. This descriptive qualitative case study used multiple data collection methods, nominal group meetings and Delphi questionnaires to explore and understand undergraduate medical students’ challenges with social learning and integration factors. These insights were then used to develop the support framework. 𝗥𝗲𝘀𝘂𝗹𝘁𝘀. The support framework articulates levels of engagement and actions required to address social learning and integrated factors, namely under- preparedness, peer support, confidence, self-management, alienation and academic advice. 𝗖𝗼𝗻𝗰𝗹𝘂𝘀𝗶𝗼𝗻. Implementing the proposed support framework on social learning and integration could facilitate the successful transition of first-year undergraduate medical students from high school to university. This framework aids students in dealing with social learning and integrated factors, such as under-preparedness, peer support, confidence, self-management and alienation as well as academic advice using contextualised and appropriate skills and tools.
Keywords: Nominal group technique; Delphi technique; social learning and integration; transition; support framework